Genetic diversity based on RAPD markers of Chenopodium ambrosioides from the cocoa region of Bahia State, Brazil - Santos, Simone Gualberto; Corrêa, Ronan Xavier (Pesquisa Agropecuaria Brasileira, 2006)
Chenopodium ambrosioides L. is known in many parts of Brazil for its medicinal properties, mainly used to control intestinal worms. Its genetic diversity is little studied. The objective of this work was to evaluate the genetic variability of 16 accessions of C. ambrosioides from the cocoa region of Bahia State, Brazil, by the RAPD technique (Random Amplified Polymorphic DNA). Only 6.9% of the 216 amplified RAPD bands were polymorphic and the pattern of dispersion of individuals showed no clustering related to sample site. Therefore, there is low variability among accessions and it is distributed among the accessions from the entire sampled region.